Potential pharmaceutical applications of sepiolite - Deasy, Alecia Rowena (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2008)
The focus of the research presented in this thesis was on the potential pharmaceutical applications of sepiolite from the Vallecas-Vicalvaro region in Spain. Initial studies involved extensive characterisation of sepiolite from this deposit, with a particular emphasis on those properties which would influence its pharmaceutical acceptability and functionality. FT-IR and pXRD indicated that the sample was of high mineralogical purity and intermediate crystallinity. SEM revealed the fibrous morphology of the sample and confirmed the absence of potentially carcinogenic long fibers. EDXA indicated that the principal elements were silicon, magnesium and oxygen, consistent with the chemical formula of sepiolite. Lower but appreciable amounts of calcium, aluminium, potassium and iron were also present. ICP-MS indicated the presence of trace levels of a number of other metals. The specific surface area of sepiolite, as determined using N2 adsorption data, was extremely high (285 mV g). 60% of the total surface area resided within micropores.
Keywords: Pharmaceutics & Pharmaceutical Technology, Ph.D.; Ph.D. Trinity College Dublin